Perdagangan Saham, Return dan Indeks LQ45 Periode 2028-2021 - Agustine Silviani; Tito Marta Sugema; Febi Mutiara Sundari (Prodi Ekonomi Syariah Universitas Majalengka, 2022)
Abstract: The discovery of market anomalies where there’s higher or lower return at a certain time so that investors can predict the movement of returns is a deviation from the concept of market efficiency. The purpose of this study is to find out and prove market efficiency through differences in stock returns and abnormal stock returns on trading days from Monday to Friday and to find out whether there are market anomalies in the form of Monday effect and weekend effect. This is quantitative research with descriptive and verifiable analysis. The population in this study is all companies whose shares are included in the LQ45 index on the Indonesia Stock Exchange during the period 2018 to 2021. The sampling technique used is purposive sampling, so that the number of samples is obtained are 28 companies. The hypothesis testing technique used are with one-sample t-test and independent samples t-test. The results showed that there was no significant difference in stock returns on the trading day from Monday to Friday, but there was a significant difference in abnormal stock returns on all five trading days, as well as market anomalies in the form of Monday effect and weekend effect on the Indonesia Stock Exchange.